Analysis of Bi-material interfacial crack with hole inclusion using boundary element method - Goh, James Yan Cheng (Nanyang Technological University, 2021)
A circular hole inclusion between the two materials is analysed, as is the association between a nearby interfacial crack between two dissimilar isotropic elastic half plates. Only tensile load acting on the matrix and perpendicular to the crack axis is taken into account. For a number of elastic combinations of the two step model, stress intensity factors are identified. The current method uses Quadratic quarter-point crack-tip element otherwise known as Quarter Node Shift (QNS) and is based upon its multi-region boundary element method (BEM). Depending on the relevant position of the hole inclusion, the crack length, and the relative elastic properties of the matrices, the interaction may have substantial shielding or strengthening effects on the stress intensity factor of the crack-tip.